Assessing the validity of the law of crime concentration across different temporal scales - Haberman, Cory P. (Journal of quantitative criminology, 2017)
Objectives The present study examined if Weisburd’s (Criminology 53(2):133–157, 2015 ) law of crime concentration held across different theoretically relevant temporal scales. Methods The cumulative percentages of Philadelphia, PA USA street blocks and intersections experiencing 25 and 50 % of street robberies by hour of the day, days of the week, and seasons of the year were compared to the bandwidth percentages established by Weisburd ( 2015 ). Different analyses were used to determine the stability of the micro-places’ street robbery levels within the three temporal scales. Results We found that the cumulative percentages of street blocks and intersections experiencing 25 and 50 % of street robberies at each of the three temporal scales closely matched the bandwidth percentages expected from Weisburd ( 2015 ) and some micro-places experienced street robberies across all temporal periods while others had more isolated temporal concentrations. Conclusion Weisburd’s ( 2015 ) law of crime concentration holds across different theoretically relevant temporal scales, and future criminology of place studies should not ignore temporal crime patterns. Further, it may be possible to refine hot spots policing approaches by incorporating spatial–temporal crime concentrations.